Nonlinear dynamic characterization of a new hysteretic device: experiments and computations - Carboni, Biagio; Lacarbonara, Walter (Nonlinear dynamics, 2016)
The nonlinear dynamical behavior of the hysteretic rheological device proposed in Carboni et al. (J Eng Mech 2014 ) is investigated. The device can provide nonlinear hysteretic forces to a one-degree-of-freedom (one-dof) mass through suitable assemblies of NiTiNOL and steel wire ropes subject to tension–flexure cycles. The simultaneous occurrence of interwire friction, phase transformations and geometric nonlinearities is the key feature of the obtained material behavior. Frequency-response curves (FRCs) of the system subject to base excitation are obtained numerically via a continuation procedure together with stability analysis and experimentally by carrying out shaking table tests, respectively. The phenomenological identification of the material behaviors through force–displacement cycles, reported in Carboni et al. (J Eng Mech 2014 ), is employed for the computation of the FRCs and the equivalent damping ratios as function of the displacement amplitude. The different restoring forces give rise to whole new families of nonlinear hysteretic oscillators governed by softening, hardening and softening–hardening behaviors depending on the oscillation amplitude.